Immune Alterations Induced by Chronic Noise Exposure: Comparison with Restraint Stress in BALB/c and C57Bl/6 Mice - Pascuan, Cecilia Gabriela (2013)
Exposure to loud noise levels represents a problem in all regions of the world. Noise exposure is known to affect auditory structures in living organisms. However, it should not be ignored that many of the effects of noise are extra-auditory. In particular, it has been proposed that noise could affect immune system similarly to other stressors. Nevertheless, only few studies so far have investigated the effects of noise on the immune function. The aim of the present work was to investigate the effect of chronic (2 wk) noise (95-97 dB) exposure on immune responses in BALB/c and C57 mice. To ascertain if the effect of noise is similar to other psychological stressors, the effect of chronic restraint –applied for the same time- on immune response was also analyzed. It was found that chronic noise impaired immune-related endpoints in vivo and ex vivo depending on the strain used. Noise, but not restraint, affected C57Bl/6 mouse T-cell-dependent antibody production and ex vivo stimulated T-cell proliferation but had no effect on these parameters in BALB/c mice or their cells. In fact, none of the stressors altered T-cell responses associated with the BALB/c mice. Further, noise exposure induced a decrease in corticosterone and catecholamines levels in BALB/c mice. In contrast, no differences were seen in these parameters for those BALB/c mice under restraint or for that matter C57Bl/6 mice exposed to restraint or noise. The results of these studies indicate that noise could seriously affect immune responses in susceptible individuals. In addition, it may also be concluded that noise possibility should not be considered a classic stressor.